Muscle lim protein isoform negatively regulates striated muscle actin dynamics and differentiation - Vafiadaki, E.; Arvanitis, DA; Papalouka, V.; Terzis, G.; Roumeliotis, T. I.; Spengos, K.; Garbis, S.D.; Manta, P; Kranias, EG; Sanoudou, D. (FEBS JFEBS JFEBS J, 2014)
Muscle lim protein (MLP) has emerged as a critical regulator of striated muscle physiology and pathophysiology. Mutations in cysteine and glycine-rich protein 3 (CSRP3), the gene encoding MLP, have been directly associated with human cardiomyopathies, whereas aberrant expression patterns are reported in human cardiac and skeletal muscle diseases. Increasing evidence suggests that MLP has an important role in both myogenic differentiation and myocyte cytoarchitecture, although the full spectrum of its intracellular roles has not been delineated. We report the discovery of an alternative splice variant of MLP, designated as MLP-b, showing distinct expression in neuromuscular disease and direct roles in actin dynamics and muscle differentiation. This novel isoform originates by alternative splicing of exons 3 and 4. At the protein level, it contains the N-terminus first half LIM domain of MLP and a unique sequence of 22 amino acids. Physiologically, it is expressed during early differentiation, whereas its overexpression reduces C2C12 differentiation and myotube formation. This may be mediated through its inhibition of MLP/cofilin-2-mediated F-actin dynamics. In differentiated striated muscles, MLP-b localizes to the sarcomeres and binds directly to Z-disc components, including alpha-actinin, T-cap and MLP. The findings of the present study unveil a novel player in muscle physiology and pathophysiology that is implicated in myogenesis as a negative regulator of myotube formation, as well as in differentiated striated muscles as a contributor to sarcomeric integrity.
Keywords: Actins/*metabolism; Alternative Splicing; Amino Acid Sequence; Animals; Cell Differentiation; Cell Line; Humans; LIM Domain Proteins/blood/chemistry/genetics/*metabolism; Mice; Muscle Development; Muscle Proteins/blood/chemistry/genetics/*metabolism; Muscle, Skeletal/metabolism; Muscle, Striated/*cytology; Myoblasts/physiology; Neuromuscular Diseases/physiopathology; Protein Isoforms/metabolism; Sequence Alignment